Heterogeneous nature of the carbonaceous chondrite breccia Aguas Zarcas – Cosmochemical characterization and origin of new carbonaceous chondrite lithologies. (1st October 2022) - Kerraouch, Imene; Kebukawa, Yoko; Bischoff, Addi; Zolensky, Michael E.; Wölfer, Elias; Hellmann, Jan L.; Ito, Motoo; King, Ashley; Trieloff, Mario; Barrat, Jean-Alix; Schmitt-Kopplin, Phillipe; Pack, Andreas; et al.
Abstract: On April 23rd, 2019, the Aguas Zarcas meteorite fall occurred in Costa Rica. Because the meteorite was quickly recovered, it contains valuable extraterrestrial materials that have not been contaminated by terrestrial processes. Our X-ray computed tomography (XCT) and scanning electron microscopy (SEM) results on various pre-rain fragments from earlier work (Kerraouch et al., 2020; 2021) revealed several distinct lithologies: Two distinct metal-rich lithologies (Met-1 and Met-2), a CM1/2 lithology, a C1 lithology, and a brecciated CM2 lithology consisting of different petrologic types. Here, we further examined these lithologies in the brecciated Aguas Zarcas meteorite and report new detailed mineralogical, chemical, isotopic, and organic matter characteristics. In addition to petrographic differences, the lithologies also display different chemical and isotopic compositions. The variations in their bulk oxygen isotopic compositions indicate that the various lithologies formed in different environments and/or under diverse conditions (e.g., water/rock ratios). Each lithology experienced a different hydration period during its evolution. Together, this suggests that multiple precursor parent bodies may have been involved in these processes of impact brecciation, mixing, and re-assembly. The Cr and Ti isotopic data for both the CM1/2 and Met-1 lithology are consistent with those of other CM chondrites, even though Met-1 displays a significantly lower ε 50 Ti isotopic composition that may be attributable to sample heterogeneities on the bulk meteorite scale and may reflect variable abundances of refractory phases in the different lithologies of Aguas Zarcas. Finally, examination of the organic matter of the various lithologies also suggests no strong evidence of thermal events, but a short-term heating cannot completely be excluded. Raman parameters indicate that the peak temperature has been lower than that for Yamato-793321 (CM2, ∼400 °C). Considering the new information presented in this study, we now better understand the origin and formation history of the Aguas Zarcas daughter body.